Women in Parliament and Public Health Expenditure: Evidence from Sub-Saharan African Countries - Fokam, Gael; Mbengono, Paloma; Sato, Guilain; Noumessi, Willy; Tadadjeu, Dessy-Karl (Journal of Social Economics Research, 2021)
The linkages between women in politics and economic development have received significant attention from policymakers and researchers. There is a consensus in political economy literature that women are more sociable than men and that the higher number of females in parliament is associated with lower levels of corruption, better quality of environment and a higher level of economic growth. This paper investigates the effect of female representation on public health expenditure on a panel of 40 sub-Saharan African countries from 1995 to 2014. The empirical evidence is based on the ordinary least squares (OLS) method and the instrumental variables (IV-2SLS). The results show that a higher number of women in parliament increases the share of public spending devoted to health. Based on these results, several policy implications can be drawn.